Die finnlandschwedische Bevölkerung und die Sprachverhältnisse in Finnland - Klövekorn, Martin (ERDKUNDE, 1958)
The paper deals with problems of population and social geography of the Swedish speaking population of Finland. In the first section the general characteristics of the Fenno-Swedish population are outlined. The Fenno- Swedes, numbering about 350,000 (8 per cent, of the total) are mainly the descendants of Swedish settlers who came to the coastal areas of Finland during the Middle Ages. Today Swedish Finland consists of two parts; a northern (Swedish Osterbotten) and a southern (Aland, Aboland, Swedish Nyland). The Swedish population of Finland is distinguished from the Finnish not merely linguistically but also racially and culturally. In public life both languages are accorded the same rights; there are, for instance, Swedish schools, Swedish chairs at the Universities and a separate Fenno-Swedish political party. These two population groups also differ in occupational structure. Of the Swedisch section a greater proportion is engaged in seafaring, commerce and administration, whilst the Finnish section shows no preponderance in any particular occupations, except perhaps in industry. This difference is partly due to the fact that the Swedish population is concentrated in the coastal areas and in the towns. But even in any one city, e. g. Helsinki (Helsingfors), the same distinction is apparent. The two ethnical groups also show a different social structure; the Finnish section is spread through all social strata and is relatively strong amongst the working class, whereas the Swedish population belongs largely to the middle classes. This feature is the heritage of the former situation when Swedish was the only recognized language in administration, the law courts, the forces and in higher education and because the Finnish language has gained equality and virtual preponderance only since the middle of the last century, the change being brought about by the national Finnish movement. Another outcome of this struggle was that the Fenno-Swedish group also awoke to a national consciousness of their own. Thus both linguistic groups tend to live self-contained lives today but nevertheless they have a strong feeling of cohesion as single nation due to their common Lebensraum and history. The second section of the paper deals with the question of the differential rate of increase of the two ethnical groups. Whilst the Finnish population has grown steadily over the last decades, the Swedish group has been virtually static since 1910. There are three groups of reasons for this phenomenon: 1) The Finnish group had a more advantageous demographic development whilst the more urbanized Swedish group is over-aged and has thus a relatively lower birth rate as well as a higher death rate; due to this urbanisation, its fertility is also less. 2) Emigration was very much greater amongst the Swedish section, in particular from Aland and Osterbönen. 3) In case of mixed marriages the language adopted by the children is usually the prevalent language of the area. Since most of the mixed marriages took place in Finnish speaking towns the number of the resulting children adopting Finish was greater. The third section deals with the problem of Fennocizing the Swedish speaking areas and presents some results of a more detailed work which is to be published in due course. Whereas the Fenno-Swedish regions by the end of the last century were inhabited almost exclusively by Swedish speaking people they are today linguistically largely mixed, particularly in the southern areas. The reasons may be found mostly in internal population shifts which were set in motion by industrialisation and urbanisation since the end of the last century. The Swedish population moved very largely to the towns, particularly to Helsingfors, the Finnish people took over the agricultural holdings which had thus become available. Furthermore industry which developed in rural districts attracted many Finnish workers. The main periods of the Fenno-cizing process were the end of the last century to World War I and since World War II; in the latter case due mainly to the re-settlement of Karelian refugees. For the towns the following points have been decisive for the influx of Finns: a) the economic development since the end of the last century; b) the economic structure (on the whole it has been industrial towns and ports which attracted the Finns); c) the situation and size of their hinterland, in particular how far it reached into the Finnish speaking part of the country. Within the larger towns, and particularly as regards Helsinki, a linguistic differentiation can be noted in the way that, compared with working class areas and the most recent quarters, Swedish predominates in the older quarters as well as the superior residential areas.